Model Prediction Based Direct Power Control Strategy for Three-level PWM Converter - Huimin LI; Hui LI; Xinqiao FAN (发电技术, 2019)
To meet the requirements of fast power response speed for pulse width modulation (PWM) type converter and constant switching frequency for insulated gate bipolar transistor (IGBT), a direct power control strategy based on model prediction was proposed for three-level PWM converter. The double closed-loop control was adopted in this strategy, namely voltage outer-loop and power inner-loop. The phase-locked loop in the outer-loop is omitted, which simplifies the structure of the control system. A PI regulator is not need in the inner-loop, which makes parameters' design simple and the response speed fast. A model of three-level neutral point clamp type PWM converter was built in MATLAB/SIMULINK. The effects between the presented control strategy and traditional PI control were analyzed. The simulation results show that the new control strategy effectively reduces the total harmonic distortion rate of the AC-side current, improves the AC-side power factor, and has good dynamic and steady-state characteristics.